PENERAPAN LEMBAGA PEMASYARAKATAN TERBUKA BERDASARKAN PERATURAN PEMERINTAH NOMOR 32 TAHUN 1999 TENTANG SYARAT DAN TATA CARA PELAKSANAAN HAK WARGA BINAAN PEMASYARAKATAN DI LEMBAGA PEMASYARAKATAN PEKANBARU - H, MASTIJA; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
As human beings, prisoners also have rights that must be respected and upheld by the state, government, law. In providing guidance punishment and the only rights that are deprived of freedom of movement, while the other rights are still owned by the inmates. One fairly important rights given to prisoners is the right to be assimilated. Currently entitlement to assimilate quite often implemented. It is caused due to excess capacity experienced by the majority of correctional institutions, as happened in the Penitentiary in the city of Pekanbaru. Thus formed Penitentiary Open as a place for inmates assimilate, as well as to where to move prisoners, so that excess capacity in prisons can be resolved beforehand. Writing objective of this thesis was to determine (1) How is the process of formation of inmates at the Correctional Institution Class III Open of Rumbai (2) Are the obstacles encountered in the process of formation of inmates at the Correctional Institution Class III Open of Rumbai and (3) How can the efforts made in addressing constraints faced in the process of formation of inmates at the Correctional Institution Class III Open of Rumbai?This research uses sociological research that the correlation between law and society. This study also uses primary data, secondary data, and the data tertiary. From the research we concluded that the activities carried out in the Correctional Institution Class III Open of Rumbai is a form of guidance such as working and making skills. However, the infrastructure at the Correctional Institution Class III Open of Rumbai inadequate. That's because the old prisons are still relatively new. In efforts to address the constraints that exist at the Correctional Institution Class III Open of Rumbai this is to make money results from the prisoners work as capital in development activities in prisons.Keyword: Application-Open Prisons- Prisoners' Rights